Ethnobotanical Studies of Medicinal Plants Used in Managing Diabetes mellitus in Rejang Lebong Districts, Bengkulu - Indonesia - Sri Endarti Rahayu; Yusi Marisa; Ikhsan Matondang (Biosaintifika: Journal of Biology & Biology Education, 2021)
Diabetes mellitus is becoming a major cause of concern throughout the world. Many people, especially in rural communities, use medicinal plants to treat the disease and its complications. This study aimed to document the medicinal plant species used to manage diabetes mellitus and traditional knowledge of local communities in Curup Tengah, Rejang Lebong district, Bengkulu, Indonesia. This study was conducted using a semi-structured questionnaire targeting 32 diabetic patients, and 2 traditional healers. Twenty women (58.8%) and 14 men used medicinal plants to manage the disease. Furthermore, 44 plant species belonging to 34 botanical families were found. The Fabaceae family (9.1%) contributes the highest number of medicinal plant (4 species) followed by Zingiberaceae (3 species) and Asteraceae (2 species). Leaves (38.63%), fruit (18.18%), and seeds (13.36%) were the predominant parts used to prepare the medicine through the extraction method. Documentation of medicinal plants used to treat diabetes as a foundation for subsequent scientific research, with a focus on plants with a high level of informant consensus. Plants with low UV levels, on the other hand, need bioactive screening to confirm their use for the condition. This could be interpreted as a sign of potential plants for the discovery of novel medications. Smallanthus sonchifolius and Anredera cordifolia are reported for the first time as being used in the traditional treatment of diabetes in this study.